Tertiary Students’ Challenges Toward the Use of Oral Presentation in Speaking Class - Raihan Utami, Alvi; Amalia, Lulu Laela (Future Science, 2024)
The use of oral presentations is expected to develop students’ language skills. It helps the students to practice for improving students’ communicative competence. However, the oral presentation was challenging for EFL students. Therefore, this study attempted to investigate students' obstacles in using oral presentations during their performance. The participants of the study were twenty-one first-year students of English Education Study Program at a university in Lampung. This study used qualitative study and the data were gained by delivering a Likert scale questionnaire to the students on their perspectives towards the use of oral presentation during one semester adapted from Nouh et al. (2015). In addition to this, an interview was used to verify the data and gain further information in depth. The result showed that two main factors brought challenges for students during oral presentation, they were personal traits and presentation skills. In addition, these two common factors should be put in attention during the process of learning oral presentation. Furthermore, the conclusion of the study showed that most of the students felt anxious, nervous, and not well-prepared during oral presentations.